HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN OBESITAS SENTRAL DENGAN TEKANAN DARAH PADA ANGGOTA BATALYON X - Annisa Kusumarahmawati, (2023)
Background: Triggers someone have high blood pressure is a related sedentary lifestyle leading to overweight and obesity. Main factor in hypertension have excess fat in the body causes tissues. Tentara Nasional Indoneisa (TNI), must have excellent healt fitness. Purpose: This research is to prove the relationship between body mass index and central obesity with blood pressure in members of batalyon x. Methods: The method used is a cross-sectional quantitative approach. The sample in this study was 62 people. Results: The hypothesis test showed that the p-value between BMI and TDS was p = 0.021 and the p-value between BMI and TDD was p = 0.00. The p value between Central Obesity and TDS p = 0.00 and the p value between Central Obesity and TDD p = 0.02 or p < 0.05. The correlation coefficient between BMI and systolic blood pressure r = 0.293 and the correlation coefficient between BMI and TDS r = 0.431, then the correlation coefficient between Central Obesity and TDS r = 0.433 and the correlation coefficient between Central Obesity and TDD r = 0.390. Conclusion: There is a significant relationship between body mass index and central obesity with blood pressure in members of batalyon x.